In vitro effects of G-Protein coupled receptor 120 agonist on osteoblast differentiation and activity in osteosarcoma cells - Kasonga, Abe Dr (University of Pretoria, 2022)
Dissertation (MSC (Human Physiology))--University of Pretoria, 2022.